Effect of surface density of states and dielectric constant on the transferred charges (Qsc) of triboelectric nanogenerators: Analytical and numerical study. Issue 183 (2nd September 2017) - Ha, J.; Kim, S. M.; Kim, J.-B.
ABSTRACT: A theoretical model of the transferred charges from the contact-mode triboelectric nanogenerator (TENG) was performed in this work. Based on the analytical model, a triboelectric charge density consisting of structural parameters and averaged surface DOS ( ) was used to calculate the transferred charges, ( Qsc ), and the relationship between the Qsc, the dielectric constant, and the was investigated. The model presented here is the first use of the parameter-dependent triboelectric charge density to derive the transferred charges. This can provide practical guidance on TENG design in energy harvesting application.